Secuestro de carbono en aguaje (Mauritia flexuosa L.F.), en el centro de investigación y enseñanza forestal, Puerto Almendra, Loreto, 2021 - Reyna Gómez, Lady Milagros (2023)
The aguajal is one of the ecosystems that has environmental value in different areas and site conditions. The excess of greenhouse gasses, mainly carbon dioxide, plays a very important role (CO2 ) in the atmosphere and at the same time enhances climate warming. The main objective of the study is to sequester carbon in aguaje palm plantations (Mauritia flexuosa L.F.) of the Puerto Almendra Forestry Research and Teaching Center. All aguaje palm trees in two-ha plantations were evaluated. The results show that there are 715 aguajes palm trees; 457 (63,91%) palm trees in plot one and 258 (36,08%) palm trees in plot two. It has an average of 0,18 t of aboveground biomass in plot one and 0,28 t of aboveground biomass in plot two; on average it contains 0,09 tC carbon stored in plot one and 0,14 tC carbon stored in plot two and sequestered an average of 0,32 tCO2 in plot one and 0,51 tCO2 in plot two. The normality test of CO2 sequestration was carried out They do not have a normal distribution, they do not have homogeneity of variances, and the non parametric Wilcoxon independence test modified by Mann-Whitney or also called the Mann Whitney U test gives the p value= 0,0001 less than the level of significanceα = 0.05; which indicates that there is a very highly significant difference in carbon sequestration in the plantationMauritia flexuosa L.F. “aguaje”.